Argumen Penafsiran Tekstualis versus Kontekstualis tentang Kepemimpinan Perempuan - Sofia Rosdanila Andri (Refleksi, 2014)
The main problem discussed in this writing is a discourse of women qiwāmah (leadership) within the text. Several Qur’ānic verses are placed to legitimize opinions stated by textualists and contextualists people. This writing will discuss Qur’ānic interpretation through both parties, as well as causes which create the differences in between them. It uses historical approach and eclectical paradigm as well.Keywords: Gender, women leadership, tafsir.DOI: 10.15408/ref.v13i6.999